Discrete element method simulation of wheat bulk density - Petingco, Marvin Carpena (Kansas State University, 2020)
Bulk density indicates how much weight of material can be packed in a bin, truck, or any container used for storage or transportation. Stored grain bulk density is higher than the standard bushel test weight because of the overburden pressure and handling practices. The material and equipment properties, and widely varying interactions between kernels add to the complexity of analyzing bulk density changes in stored grain. The influence of these factors on wheat bulk density was investigated and wheat bulk density was simulated using the discrete element method (DEM). The objectives of this research were to: (1) experimentally investigate the influence of kernel shape and size on packing ratio and compressibility of wheat, (2) determine the influence of particle shape and contact parameters on DEM-simulated bulk density, (3) simulate using DEM the bulk density of wheat as affected by grain drop height and size distribution, and (4) simulate using DEM the bulk density of wheat as affected by overburden pressure. Laboratory experiments showed that packing ratio (compressibility) had strong positive (negative) linear relationship with sphericity and flatness shape factors but strong negative (positive) linear relationship with elongation shape factor. Also, the higher percentage of mass of larger kernel fraction in a mixture contributed to higher packing ratio and lower compressibility. DEM simulation showed that decreasing aspect ratio and geometrical smoothness of particles increased simulated bulk density of wheat. Among the pseudo-ellipsoidal particle models, the five-sphere particle was the best option to represent wheat particles, while among the contact parameters, the wheat-to-wheat coefficient of static friction and wheat-to-wheat rolling friction had the greatest influence on simulated bulk density. Wheat bulk density as affected by drop height and percentage composition of the three kernel fractions can be simulated accurately using either single-sphere or five-sphere pseudo-ellipsoidal particle, provided that the contact parameters of each particle model representing each size fraction were calibrated individually. DEM simulation of wheat under confined uniaxial compression was implemented to determine the effect of overburden pressure on wheat bulk density. Results showed that the appropriate time step, grid size, and pressure loading rate had to be determined first to avoid instabilities and erroneous results. The DEM simulated bulk densities agreed with the experimental results for overburden pressure below 48kPa and tend to overpredict at higher overburden pressure. This study contributed to better understanding of the influence of particle shape, contact parameters, drop height, overburden pressure, and size distribution on bulk density and provides an approach on how to simulate wheat bulk density using DEM as affected by these factors. These findings can be used in developing accurate models for estimating bulk density and grain packing in bins and other storage structures.
Keywords: Discrete element method; Bulk density; Wheat compressibility; Wheat packing; Particle shape; Particle size distribution